Effect of Strength Training on Pain Reduction and Physical Function Improvement in Postoperative Prostate Cancer Patients - Wisnu Guntur Prakoso; Tadi Tadi; Achmad Fauzi; Navy Sealsi Adinda Prisca Marina; Tintin Sukartini (Universitas Malahayati, 2026)
ABSTRACT Nursing has an important role in improving the health and prevention of complications of post-surgical patients. One of the nursing interventions that can be provided is Pelvic Floor Muscle Exercise (Kegel) which aims to strengthen the muscles that support the bladder and intestines, which are often affected after prostate surgery. To systematically explore the effect of strength training on reducing pain and improving physical function in postoperative prostate cancer patients. The method uses a search through 4 major databases namely PubMed, Scopus, Sciencedirect and ProQuest with a range of 5 years from 2020 to 2025. The literature search used keywords namely